What Customers Value Most: The Real Impact of CSR in Islamic Banking in Indonesia and Turkey - Mauluddi, Hasbi Assidiki; Natasya, Putri Aulia; Ningrat, Putri Ayu; Latif, Dini Verdania (Indonesian Journal of Economics and Management, 2025)
This study aims to examine the influence of customer perception of Corporate Social Responsibility (CSR) and the actual implementation of CSR initiatives on customer satisfaction in the context of Islamic banking in Indonesia and Turkey. Using a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from 215 respondents in Indonesia and 175 respondents in Turkey who are active customers of Islamic banks. The results reveal significant differences between the two countries. In Indonesia, CSR implementation has a strong and significant impact on customer satisfaction, while customer perception of CSR does not show a statistically significant effect. Conversely, in Turkey, both customer perception and CSR implementation significantly influence customer satisfaction, although with more moderate effect sizes. These findings highlight the contextual role of cultural and institutional factors in shaping how CSR is received and valued by customers. The study concludes that tangible CSR actions have a stronger influence than perception alone, particularly in Indonesia, and that effective CSR communication and strategic customer involvement are essential to enhancing satisfaction. The study provides practical recommendations for Islamic banks to strengthen their CSR strategies by aligning them with sharia principles, ensuring transparency, expanding strategic focus areas, and actively engaging customers in social initiatives.